Indonesia Analisis dampak pencemaran udara perkotaan dan strategi pengendalian yang efektif - dermayanti, nirmawala masna (Maliki Interdisciplinary Journal, 2026)
Air pollution in urban areas has become an increasingly serious environmental problem due to the rapid growth of transportation, industrial activities, and population density. This study aims to examine the impacts of air pollution on public health, urban environmental conditions, as well as social and economic aspects, while also analyzing effective control strategies. The method used in this research is a literature review by examining various relevant scientific journals and previous studies. The results indicate that air pollutants such as PM2.5, CO, NO₂, and SO₂ can cause serious health problems, particularly respiratory and cardiovascular diseases. In addition to affecting human health, air pollution also contributes to rising urban temperatures, ecosystem degradation, increased healthcare costs, and reduced community productivity. Air pollution control efforts can be implemented through stricter emission policies, the development of environmentally friendly transportation, expansion of green open spaces, and the utilization of Internet of Things (IoT) and machine learning technologies for real-time air quality monitoring. Therefore, collaboration among the government, society, and related stakeholders is essential to create a healthy and sustainable urban environment.